Implementasi Program GHIPPA dalam Meningkatkan Kebutuhan Irigasi Air - Sony Susanto; Ana Komari; Hendy Hendy; Afiff Yudha Triparianto; Ahmad Faizal Efendi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
The government has an important role so that the implementation of the fulfillment of community food is carried out the same as the fulfillment of other rights. Therefore, efforts to fulfill community food are a serious problem in development programs, both those that have been launched by the Regional Government and the Central Government. Efforts to fulfill food by the Regional Government by realizing food availability are also carried out by the government in Java. Java Island itself is the center of rice production in Indonesia because it is able to produce the largest rice production, especially East Java Province with a total production of 12,198,707 tons. The aim of this community service is to increase socialization of the GHIPPA program to meet the water irrigation needs of the village. In order to achieve this target, the Nganjuk Regency Government has started implementing various programs to increase agricultural production. However, there is a major obstacle to increasing production,  namely  the  availability  of  deep  water.  Therefore,  the  Nganjuk Regency  Government  is  trying  to  overcome  the  availability  of  water.  These include providing irrigation network infrastructure, Farmer Business Level Irrigation Network/Village Irrigation Network (JITUT/JIDES), Farming Business Roads, Pumping and Empowerment of the Water User Farmers Association (GHIPPA).